2004
DOI: 10.1038/ng1295
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of flowering time by FVE, a retinoblastoma-associated protein

Abstract: The initiation of flowering in plants is controlled by environmental and endogenous signals 1,2 . Molecular analysis of this process in Arabidopsis thaliana indicates that environmental control is exerted through the photoperiod and vernalization pathways, whereas endogenous signals regulate the autonomous and gibberellin pathways. The vernalization and autonomous pathways converge on the negative regulation of FLC 3,4 , a gene encoding a MADS-box protein that inhibits flowering 3,4 . We cloned FVE, a componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
310
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(337 citation statements)
references
References 32 publications
21
310
0
6
Order By: Relevance
“…After exposure to vernalization, the sdr6 plants flowered earlier than the plants grown in LD and SD (Figure 4). This responsiveness of the sdr6 plants to GA and vernalization were similar to previous results for several autonomous pathway mutants (Ausin et al 2004;Henderson et al 2005;Mockler et al 2004). In addition, transcript levels of critical genes in the autonomous pathway, i.e., FLC, LD, FVE, and SOC1 were significantly altered in sdr6 plants.…”
Section: Discussionsupporting
confidence: 78%
“…After exposure to vernalization, the sdr6 plants flowered earlier than the plants grown in LD and SD (Figure 4). This responsiveness of the sdr6 plants to GA and vernalization were similar to previous results for several autonomous pathway mutants (Ausin et al 2004;Henderson et al 2005;Mockler et al 2004). In addition, transcript levels of critical genes in the autonomous pathway, i.e., FLC, LD, FVE, and SOC1 were significantly altered in sdr6 plants.…”
Section: Discussionsupporting
confidence: 78%
“…fve-1, however, contains an Ala-to-Val missense mutation that may not represent a total loss of function. That fve-1 is not a null allele is supported by the fact that another missense mutation in Ler, fve-2, has a stronger late-flowering phenotype than fve-1 (Ausin et al, 2004). Thus, it is possible that if an fpa fve double mutant were constructed in the Ler genetic background using a null allele of fve, the double mutant may have pleiotropic phenotypes similar to those seen in the Col background.…”
Section: Discussionmentioning
confidence: 92%
“…Another cause for the differences in phenotypes are the alleles of fpa and fve used: fpa-7 and fve-4 (this study) and fpa-1 and fve-1 (Koornneef et al, 1998). fpa-1, fpa-7, and fve-4 likely represent null alleles; fpa-1 and fve-4 contain premature stop codons Ausin et al, 2004); and fpa-7 contains a T-DNA insertion (Michaels and Amasino, 2001). fve-1, however, contains an Ala-to-Val missense mutation that may not represent a total loss of function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FVE was isolated by positional cloning 17 . Linkage analysis confirmed that acg1 might be fve, an allele of FVE (Fig.…”
mentioning
confidence: 99%